Model Panel Data dalam Mengukur Determinasi Faktor-Faktor yang Berpengaruh terhadap Pembiayaan Murabahah pada Pebankan Syariah di Indonesia - Yudhistira Ardana; Dudi Septiadi; Wulandari Wulandari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Murabaha financing disbursed by Islamic banks is influenced by two factors, namely internal and external factors of the bank. The internal condition of Islamic banking can be seen through the bank's financial statements which are described in financial performance ratios. Meanwhile, to see external factors, macroeconomic variables are used. This study aims to analyze the factors that influence the murabahah financing of Islamic banks using panel data. The variables used in this study are CAR (X1), FDR (X2), Inflation (X3), and SBIS (X4) as independent variables. Murabaha financing (Y) as the dependent variable. The estimation of panel data in this study uses the best model, namely random-effect. All variables used in this study have an effect or influence of 97.16% and the remaining 2.84% is influenced by other factors outside the model. In this study, partially the CAR variable has a significant negative effect, the SBIS variable has a significant positive effect, while the FDR and inflation variables have a significant negative effect on murabahah financing of Islamic banks in Indonesia.